Burkitt lymphoma masquerading as cardiac tamponade - Kaul, Pankaj (BioMed Central, 2007)
A 61 year old man presented with diffuse large B cell lymphoma of the skin of the back of the shoulder which was excised and treated with chemotherapy (CHOP regime) in 1998. He was in complete remission till he presented in 2002 with extranodal marginal zone lymphoma of the parotid gland for which he underwent superficial parotidectomy and radiotherapy. He continued in remission till 2006 when he presented with recurrent pericardial effusion and tamponade. At median sternotomy, pericardial effusion was drained, an anterior pericardiectomy was done and a left posterior pericardial window made, and an enlarged hard paraaortic lymph node excised. Histology, immunocytochemistry and chromosome analysis revealed Burkitt lymphoma. Patient underwent chemotherapy with CODOX-M regime and continues in remission. This report is unusual on account of the highly atypical presentation of Burkitt lymphoma as cardiac tamponade, only a few cases having been reported previously, the occurrence of three lymphomas of different pathological and genomic profiles in one patient over a period of eight years and the relatively slow rate of growth of an otherwise fulminant tumour with high tumour doubling time. A review of literature with special emphasis on chromosomal diagnosis, transformation of other lymphomas into Burkitt lymphoma and mediastinal and cardiac involvement with Burkitt lymphoma is presented.